The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.54337/ijsepm.7413
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy and Inclusive Economic Development: An African Case Study

Denis Nfor Yuni,
Ndubuisi Ezenwa,
Nathaniel E. Urama
et al.

Abstract: Climate change constitutes a major challenge to economic growth and development across the globe as it negatively affects most sectors of the economy. Hence, there has been a global clamour for countries to invest in climate change mitigations. In developing regions like Africa, however, there are high resource limitations, and as such, there is a general opinion that funding climate change mitigation will have a huge opportunity cost of low investment in other development infrastructures, with the likelihood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…There is a widespread belief that because of limited financial resources for expanding renewable energy in isolated island communities and some developing regions, that prioritizing climate mitigation might lead to a significant trade-off in other crucial infrastructures, potentially reducing overall economic development prospects. Yuni et al, (2023) [9] investigated the impact of renewable electricity production and consumption in Africa and concluded that it does not only mitigate climate change but could also contribute marginally to the economic growth and development of African countries.…”
Section: Introductionmentioning
confidence: 99%
“…There is a widespread belief that because of limited financial resources for expanding renewable energy in isolated island communities and some developing regions, that prioritizing climate mitigation might lead to a significant trade-off in other crucial infrastructures, potentially reducing overall economic development prospects. Yuni et al, (2023) [9] investigated the impact of renewable electricity production and consumption in Africa and concluded that it does not only mitigate climate change but could also contribute marginally to the economic growth and development of African countries.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, Iraq heavily relies on large-scale thermal energy derived from gases released into the atmosphere [12]. However, concerted efforts to develop and harness renewable resources could significantly impact the country's future energy landscape [13][14][15][16][17]. Fossil fuels account for over 80% of Iraq's electricity generation.…”
Section: Introductionmentioning
confidence: 99%
“…International organizations acknowledge the urgency of combating climate change [1], leading to global efforts, stringent policies, and ambitious carbon neutrality targets. As governments and industries unite in their commitment to combat climate change, the transition to Electric Vehicles (EVs) emerges as a pivotal step towards achieving sustainable and environmentally responsible transportation systems.…”
Section: Introductionmentioning
confidence: 99%